Melatonin Rescues Photosynthesis and Triggers Antioxidant Defense Response in Cucumis sativus Plants Challenged by Low Temperature and High Humidity - Amin, Bakht; Atif, Muhammad Jawaad; Meng, Huanwen; Ali, Muhammad; Li, Shuju; Alharby, Hesham F.; Majrashi, Ali; Hakeem, Khalid Rehman; Cheng, Zhihui (Frontiers in Plant Science, 2022)
Environmental factors such as low temperature (LT) and high humidity (HH) hinder plant growth and development in plastic tunnels and solar greenhouses in the cold season. In this study, we examined the effect of melatonin (MT) on shoot-based tolerance to LT and HH conditions in cucumber (Cucumis sativus) seedlings, and explored the underlying mechanism. LT and HH stress inhibited growth and biomass accumulation, produced leaf chlorosis, led to oxidative stress, lowered chlorophyll and carotenoid contents, reduced photosynthetic and photosystem II (PSII) activities, and increased the level of intercellular carbon dioxide and the non-photochemical quenching of PSI and PSII. However, foliar application of MT significantly improved the morphological indices and photosynthetic efficiency of cucumber seedlings, which entailed the elevation of electrolyte leakage, lipid peroxidation, and reactive oxygen species accumulation by boosting the antioxidant enzyme defense system under LT and HH conditions. Additionally, measurement of nitrogen (N), magnesium (Mg), and iron (Fe) contents in roots and leaves showed that MT significantly augmented the nutrient uptake of cucumber seedlings exposed to LT and HH stresses. Furthermore, MT application increased the transcripts levels of genes encoding antioxidant enzymes under LT and HH conditions, whereas treatment with LT and HH suppressed these genes, suggesting that MT application increases the LT and HH tolerance of cucumber seedlings. Overall, our results suggest that MT application increases the tolerance of cucumber seedlings to LT and HH stress by enhancing the plant morphometric parameters, regulating PSI and PSII, and activating the antioxidant defense mechanism. Thus, the exogenous application of MT could be potentially employed as a strategy to improve the LT and HH tolerance of cucumber.